2019
DOI: 10.1088/1361-6501/ab310b
|View full text |Cite
|
Sign up to set email alerts
|

A novel light field imaging based 3D geometry measurement technique for turbomachinery blades

Abstract: This paper presents a novel snapshot three-dimensional (3D) imaging technique for fast turbomachinery blade geometrical measurements. The proposed measurement system employs a microlens array based light-field camera to capture 3D blade geometry into one light-field image, from which 100 new perspective images can be generated and the blade 3D point cloud can be recovered through sophisticated light-field rendering algorithms. The measurement accuracy is determined to be approximately by measuring a series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…While the technology boasts high resolution and measurement efficiency, its imaging depth is limited by current technology, precluding the ability to measure certain micropore samples at greater depths. 3) Light field imaging technology [7]. The optical field imaging technique is a method of measurement that uses the rules of micro-lens array arrangement to operate on parallax to obtain image depth information.…”
Section: Existing Researchmentioning
confidence: 99%
“…While the technology boasts high resolution and measurement efficiency, its imaging depth is limited by current technology, precluding the ability to measure certain micropore samples at greater depths. 3) Light field imaging technology [7]. The optical field imaging technique is a method of measurement that uses the rules of micro-lens array arrangement to operate on parallax to obtain image depth information.…”
Section: Existing Researchmentioning
confidence: 99%
“…They introduced a calibration method based on the features of the blade reference surface, eliminating pose errors in the system without the need for additional calibration objects. The area-source method typically employs digital image correlation techniques [13,14] or structured light technology. For example, Huang et al [15] and others proposed an efficient and highly accurate full-section blade measurement technique based on multi-view structured light three-dimensional measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Their method showed that a dual light field camera could mitigate the elongation of reconstructed particles and improve the depth resolution. Meanwhile, Shi et al used a single-camera light field PIV to measure the velocity field of a synthetic jet, a self-similar adverse pressure gradient turbulent boundary layer, and supersonic jet and turbomachinery blades [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%